2006
DOI: 10.1007/s00223-005-0163-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Insulin-Like Growth Factor (IGF); IGF-Binding Proteins-3, -4, and -5; and Their Relationships to Bone Mineral Density and the Risk of Vertebral Fractures in Postmenopausal Women

Abstract: We previously found that serum levels of insulin-like growth factor I (IGF-I) and IGF-binding protein (IGFBP)-3, but not IFGBP-2, were associated with bone mineral density (BMD) and the risk of vertebral fractures. The aim of the present study was to investigate the roles of IGFBP-4 and -5 in age-dependent bone loss and vertebral fracture risk in postmenopausal Japanese women and to compare them with those of IGF-I and IGFBP-3. One hundred and ninety-three Japanese women aged 46-88 years (mean 62.5) were enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…(25) The anabolic effects of these hormones on bone may explain the relatively maintained BMD in T2DM compared with T1DM. In clinical studies, we and others showed that serum IGF-I levels were positively correlated with BMD in non-DM populations (26)(27)(28)(29) and that the hormone level was associated with reduced risk of VFs in postmenopausal women. (26) In T2DM women, however, we previously showed that serum IGF-1 level was not significantly correlated with BMD, whereas its increase was associated with reduced VF risk.…”
Section: Yamamoto Et Almentioning
confidence: 79%
“…(25) The anabolic effects of these hormones on bone may explain the relatively maintained BMD in T2DM compared with T1DM. In clinical studies, we and others showed that serum IGF-I levels were positively correlated with BMD in non-DM populations (26)(27)(28)(29) and that the hormone level was associated with reduced risk of VFs in postmenopausal women. (26) In T2DM women, however, we previously showed that serum IGF-1 level was not significantly correlated with BMD, whereas its increase was associated with reduced VF risk.…”
Section: Yamamoto Et Almentioning
confidence: 79%
“…Although lung epithelial cancer cells and fibroblasts express IGFBP-6, the IGFBP-6 did not influence the migration of CD34 -/CD133 + cells. The IGFBP-3, which is the major IGFBP in peripheral blood (8,35), had no influence on the migration of CD34 -/CD133 + HSPCs. In contrast to CD34 -/ CD133 + cells, the migration of CD34 + /CD133 -HSPCs was not influenced by the IGFBP-2 and -4.…”
Section: Discussionmentioning
confidence: 92%
“…According to the range of concentration in human plasma or serum (8,34,35), 100-500 ng/ml rh IGF-I, 100-900 ng/ml rh IGFBP-2, 2,000-3,000 ng/ml rh IGFBP-3, 250-750 ng/ml rh IGFBP-4 or 100-500 ng/ml rh IGFBP-6 were applied. Because these rh IGF compounds are stored in 0.1% bovine serum albumin (BSA) solution, each control experiment was performed with the same amount of BSA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prospective analysis confirmed a similar association in women (van Varsseveld et al, 2015). Low IGF-1 level has been linked to increased risk of future fracture in men and women, although not all studies have shown consistent sex-specific effects (Ohlsson et al, 2011; van Varsseveld et al, 2015; Yamaguchi et al, 2006). …”
Section: Gh/igf-1 Axis and Age-related Diseasesmentioning
confidence: 99%